(untitled) (Annals of Medical Research, 2024)
Aim: Narrowing in the esophagus caused by benign conditions such as peptic injury, surgical anastomosis, radiation therapy, Schatzki rings, esophageal webs, erosive injury and eosinophilic esophagitis are called benign esophageal strictures. In the treatment of benign esophageal stricture, endoscopic dilation with balloon or bougie is the first priority. Materials and Methods: The study included a total of 96 patients who were diagnosed with a benign stricture at the gastroenterology clinic of our university from May 2009 to October 2023. All patients were symptomatic, and their main complaint was dysphagia. The benign stricture was diagnosed through clinical examination, radiological imaging and endoscopy. Patient data were scanned retrospectively. The dilation method (bougie, balloon), the number of times the procedure was permormed and any potential complications were recorded. Stents were applied to patients who did not provide adequate dilatation. Results: A total of 96 patients were included in the study. Forty-seven (49%) of them were women and 49 (51%) were men. The average age was 48±17 years (the youngest was 18, the oldest was 81). A total of 198 dilation procedures were performed on 96 patients. The average follow-up period was 79±54 (1-179) months. Srictures were divided into 4 groups according to etiology as anastomotic stricture, peptic stricture, caustic stricture and post-radiotherapy stricture. Of the cases with stricture, 76 (79.2%) underwent bougie dilation, 26 (27.1%) underwent balloon dilation, 5 (5.2%) underwent bougie and then balloon dilation, and in 5 (5.2%) cases, metallic stent was placed due to failed dilations. Conclusion: This study shows the effectiveness of bougie and/or balloon dilation in treating most of the patients with benign esophageal strictures, with a low complication rate. It is less invasive, comfortable and cost-effective than the alternative surgical approach.